Cervical cancer benefits from trabectedin combination with the β-blocker propranolol: in vitro and ex vivo evaluations in patient-derived organoids - Di Fonte, Roberta; Strippoli, Sabino; Garofoli, Marianna; Cormio, Gennaro; Serratì, Simona; Loizzi, Vera; Fasano, Rossella; Arezzo, Francesca; Volpicella, Mariateresa; Derakhshani, Afshin; Guida, Michele; Porcelli, Letizia; et al. (Frontiers in Cell and Developmental Biology, 2023)
Background: Cervical cancer (CC) is characterized by genomic alterations in DNA repair genes, which could favor treatment with agents causing DNA double-strand breaks (DSBs), such as trabectedin. Hence, we evaluated the capability of trabectedin to inhibit CC viability and used ovarian cancer (OC) models as a reference. Since chronic stress may promote gynecological cancer and may hinder the efficacy of therapy, we investigated the potential of targeting β-adrenergic receptors with propranolol to enhance trabectedin efficacy and change tumor immunogenicity. Methods: OC cell lines, Caov-3 and SK-OV-3, CC cell lines, HeLa and OV2008, and patient-derived organoids were used as study models. MTT and 3D cell viability assays were used for drug(s) IC50 determination. The analysis of apoptosis, JC-1 mitochondrial membrane depolarization, cell cycle, and protein expression was performed by flow cytometry. Cell target modulation analyses were carried out by gene expression, Western blotting, immunofluorescence, and immunocytochemistry. Results: Trabectedin reduced the proliferation of both CC and OC cell lines and notably of CC patient-derived organoids. Mechanistically, trabectedin caused DNA DSBs and S-phase cell cycle arrest. Despite DNA DSBs, cells failed the formation of nuclear RAD51 foci and underwent apoptosis. Under norepinephrine stimulation, propranolol enhanced trabectedin efficacy, further inducing apoptosis through the involvement of mitochondria, Erk1/2 activation, and the increase of inducible COX-2. Notably, trabectedin and propranolol affected the expression of PD1 in both CC and OC cell lines. Conclusion: Overall, our results show that CC is responsive to trabectedin and provide translational evidence that could benefit CC treatment options. Our study pointed out that combined treatment offset trabectedin resistance caused by β-adrenergic receptor activation in both ovarian and cervical cancer models.